A battery cell, a method of manufacturing the same, and an electric device
By setting phosphide and fluoride modification layers at the interface of solid-state batteries, the problem of poor cycle performance caused by lithium dendrite growth is solved, low interface impedance and high critical current density are achieved, and the cycle stability and safety of the battery are improved.
Patent Information
- Application Number
- CN202611511230.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-11-03
AI Technical Summary
In existing solid-state batteries, the SEI film formed at the interface when the lithium metal anode comes into contact with the solid electrolyte is a mixed electron-ion conductive interface, which allows electrons to pass through, resulting in thickening of the interface layer, increased interface impedance, and lithium dendrite growth, which seriously deteriorates cycle performance and electrochemical performance.
An interface modification layer, including a phosphide modification layer and a fluoride modification layer, is set between the solid electrolyte and the negative electrode. The phosphide modification layer serves as a lithium-ion transport channel, and the fluoride modification layer serves as an electron barrier. Li3P and LiF layers are formed by magnetron sputtering and spin coating, and their thickness and ratio are controlled to optimize the interface characteristics.
It reduces the interfacial impedance between the solid electrolyte and the negative electrode, improves the uniformity of lithium-ion flow and the cycle stability of the battery, and enhances the cycle performance under high current.
Smart Images

Figure CN123034014A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery manufacturing technology, and in particular to a battery cell, its manufacturing method, and an electrical device thereof. Background Technology
[0002] Solid-state batteries are a type of secondary battery system that uses a solid electrolyte instead of the traditional liquid or gel electrolyte. Compared to traditional liquid batteries, solid-state batteries offer higher safety and energy density.
[0003] When solid-state batteries use lithium metal as the negative electrode, due to the strong reducing properties of lithium metal, when the solid electrolyte comes into contact with lithium metal, the high-valence metal elements in the solid electrolyte will be quickly reduced to elemental metals. This results in the solid electrolyte interphase (SEI) film formed at the interface being a mixed electron-ion conductive interface. The SEI film with LiCl as the main component has the disadvantages of low ionic conductivity and inability to block electron transport. Its critical current density (CCD) is almost 0, which leads to the continuous thickening of the SEI and the growth of lithium dendrites, which seriously deteriorates the cycle performance and electrochemical performance of the solid-state battery. Summary of the Invention
[0004] The main objective of this invention is to propose a battery cell, its preparation method, and an electrical device thereof, aiming to solve the problem of poor cycle performance of solid-state batteries in the prior art.
[0005] To achieve the above objectives, the present invention proposes a battery cell, the battery cell comprising a positive electrode, a negative electrode, an interface modification layer, and a solid electrolyte, wherein the interface modification layer is disposed between the solid electrolyte and the negative electrode; the negative electrode comprises elemental lithium metal. The interface modification layer includes a phosphide modification layer and a fluoride modification layer, wherein the phosphide modification layer is disposed on the side of the fluoride modification layer close to the negative electrode sheet; The phosphide-modified layer includes a Li3P layer, and the fluoride-modified layer includes a LiF layer.
[0006] In one embodiment, the thickness of the phosphide-modified layer is 20 nm to 400 nm.
[0007] In one embodiment, the thickness of the fluoride-modified layer is 5 nm to 100 nm.
[0008] In one embodiment, the thickness ratio of the phosphide-modified layer to the fluoride-modified layer is 5:3 to 10:3; and / or, The solid electrolyte includes at least one of halide solid electrolyte, sulfide solid electrolyte and oxide solid electrolyte, wherein the halide solid electrolyte includes at least one of Li2ZrCl6 and Li3YCl6.
[0009] The present invention also provides a method for preparing a battery cell, the method comprising the following steps: Solid electrolytes, negative electrode plates, and positive electrode plates are provided; The solid electrolyte is bonded to the negative electrode to form an intermediate; wherein an interface modification layer is formed between the solid electrolyte and the negative electrode. The intermediate and the positive electrode are assembled to obtain a battery cell.
[0010] In one embodiment, the method for forming the interface modification layer includes at least one of magnetron sputtering, vapor deposition, solution impregnation, and spin coating.
[0011] In one embodiment, the surface of the solid electrolyte near the negative electrode is a first side surface, and the surface of the negative electrode near the solid electrolyte is a second side surface. The step of bonding the solid electrolyte to the negative electrode sheet to form an intermediate includes: A fluoride modification layer is formed on the first side surface by magnetron sputtering to obtain the modified first side surface. A phosphide solution is spin-coated onto the second side, the solvent is removed to form a phosphide solid film, and then vacuum drying is performed to form a phosphide modification layer on the second side, resulting in a modified second side. The first side modified with solid electrolyte and the second side modified with negative electrode are bonded together to obtain an intermediate.
[0012] In one embodiment, in the step of forming a fluoride modification layer on the first side surface by magnetron sputtering to obtain the modified first side surface: The pressure of the magnetron sputtering method is 0.5~1.0 Pa; and / or, The power of the magnetron sputtering method is 25~35W; and / or, The magnetron sputtering time is 250~350s.
[0013] In one embodiment, the step of spin-coating a phosphide solution onto the second side, removing the solvent to form a phosphide solid film, and then performing vacuum drying to form a phosphide-modified layer on the second side, thereby obtaining the modified second side: The spin coating includes spin coating at 550-650 rpm for 8-12 seconds, followed by spin coating at 2500-3500 rpm for 25-35 seconds; and / or, The concentration of the phosphide solution is 0.05~0.1M; and / or, The phosphide solution contains at least one of triphenylphosphine and trioctylphosphine; and / or, The vacuum drying process includes heating from 20~25℃ to 80~120℃ and holding at that temperature for 25~35 minutes, followed by heating to 125~135℃ and holding at that temperature for 1.5~2.5 hours.
[0014] The present invention also provides an electrical device, the electrical device comprising the aforementioned battery cell or a battery cell prepared by the aforementioned battery cell preparation method.
[0015] In the technical solution of this invention, an interface modification layer is provided between the solid electrolyte and the negative electrode. The phosphide modification layer contains Li3P, which has high ionic conductivity. By placing it on one side of the negative electrode, it can serve as a lithium-ion transport channel, significantly reducing the interface impedance between the solid electrolyte and the negative electrode, improving rate performance. It also modifies surface defects on the negative electrode, reducing noticeable protrusions and improving the uniformity of lithium-ion flow. However, due to its high ionic conductivity, Li3P in the phosphide modification layer does not significantly inhibit lithium dendrite formation. When lithium dendrites form, their growth rate accelerates, leading to battery failure. The fluoride modification layer contains LiF, which has excellent electronic insulation and high interface energy. As a physical and chemical barrier, it effectively blocks electron migration from the electrolyte to lithium metal. By inhibiting electron tunneling, it blocks the lithium dendrite tips penetrating the Li3P layer, preventing further development. This better resists battery volume changes and dendrite growth under high current densities, thus significantly improving the battery's cycle stability. Therefore, the battery cell provided by the present invention has both low interface impedance and high critical current density, and its cycling performance under high current is good. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0017] Figure 1 This is a morphology diagram of the lithium metal anode surface after 50 cycles at 1C for the full cell (the positive electrode is lithium iron phosphate) corresponding to Comparative Example 4 of the present invention. Figure 2 This is a morphology diagram of the lithium metal anode surface after 50 cycles at 1C for the full cell (the positive electrode is lithium iron phosphate) corresponding to Example 1 of the present invention.
[0018] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, or solution B, or a solution where both A and B are satisfied simultaneously. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] When solid-state batteries use lithium metal as the negative electrode, due to the strong reducing properties of lithium metal, when the solid electrolyte comes into contact with lithium metal, the high-valence metal elements in the solid electrolyte will be quickly reduced to elemental metals. This results in the solid electrolyte interphase (SEI) film formed at the interface being a hybrid electron-ion conductive interface. This interface can conduct both lithium ions and electrons. Since electrons can penetrate this interface layer, the electrolyte is continuously reduced and decomposed during battery cycling, the interface layer thickens, and this leads to increased interface impedance and lithium dendrite growth, which seriously deteriorates the cycle performance and electrochemical performance of the solid-state battery.
[0021] In view of this, the present invention proposes a battery cell, the battery cell comprising a positive electrode, a negative electrode, an interface modification layer, and a solid electrolyte, wherein the interface modification layer is disposed between the solid electrolyte and the negative electrode; the negative electrode comprises elemental lithium metal; the interface modification layer comprises a phosphide modification layer and a fluoride modification layer, wherein the phosphide modification layer is disposed on the side of the fluoride modification layer closer to the negative electrode; the phosphide modification layer comprises a Li3P layer, and the fluoride modification layer comprises a LiF layer.
[0022] In the technical solution of this invention, an interface modification layer is provided between the solid electrolyte and the negative electrode. The phosphide modification layer contains Li3P, which has high ionic conductivity. By placing it on one side of the negative electrode, it can serve as a lithium-ion transport channel, significantly reducing the interface impedance between the solid electrolyte and the negative electrode, improving rate performance. It also modifies surface defects on the negative electrode, reducing noticeable protrusions and improving the uniformity of lithium-ion flow. However, due to its high ionic conductivity, Li3P in the phosphide modification layer does not significantly inhibit lithium dendrite formation. When lithium dendrites form, their growth rate accelerates, leading to battery failure. The fluoride modification layer contains LiF, which has excellent electronic insulation and high interface energy. As a physical and chemical barrier, it effectively blocks electron migration from the electrolyte to lithium metal. By inhibiting electron tunneling, it blocks the lithium dendrite tips penetrating the Li3P layer, preventing further development. This better resists battery volume changes and dendrite growth under high current densities, thus significantly improving the battery's cycle stability. Therefore, the battery cell provided by the present invention has both low interface impedance and high critical current density, and its cycling performance under high current is good.
[0023] In some embodiments, the thickness of the phosphide-modified layer is 20 nm to 400 nm. The thickness of the phosphide-modified layer can be 20 nm, 50 nm, 100 nm, 200 nm, or 400 nm. Controlling the thickness of the phosphide-modified layer within the above range can ensure a significant reduction in the interfacial impedance of the battery and an increase in the critical current density.
[0024] In some embodiments, the thickness of the fluoride-modified layer is 5 nm to 100 nm. The thickness of the fluoride-modified layer can be 5 nm, 10 nm, 50 nm, 80 nm, or 100 nm. Controlling the thickness of the fluoride-modified layer within the above range can ensure a high critical current density and long cycle life of the battery, while also improving the interface impedance.
[0025] In some embodiments, the thickness ratio of the phosphide-modified layer to the fluoride-modified layer is 5:3 to 10:3; and / or, the solid electrolyte includes at least one of a halide solid electrolyte, a sulfide solid electrolyte, and an oxide solid electrolyte. That is, the thickness ratio of the phosphide-modified layer to the fluoride-modified layer can be 5:3, 6:3, 7:3, 8:3, 9:3, or 10:3. Controlling the thickness ratio within a suitable range ensures that the battery has both low interfacial impedance and high critical current density, ultimately improving the battery's cycle life.
[0026] The halide solid electrolytes include at least one of Li₂ZrCl₆ and Li₃YCl₆; the oxide solid electrolytes include Li₇La₃Zr₂O. 12 Li1.3 Al 0.3 Ti 1.7 At least one of (PO4)4; sulfide solid electrolytes include Li6PS5Cl, Li 10 GeP2S 12 At least one of the following. The solid electrolyte is preferably a halide solid electrolyte, which has better processing flexibility, ionic conductivity and high-voltage cathode compatibility.
[0027] The present invention also provides a method for preparing a battery cell, the method comprising the following steps: Step S1: Provide a solid electrolyte, a negative electrode, and a positive electrode; Step S2: The solid electrolyte is bonded to the negative electrode to form an intermediate; wherein an interface modification layer is formed between the solid electrolyte and the negative electrode. Step S3: Assemble the intermediate and the positive electrode to obtain a battery cell.
[0028] In the technical solution of this invention, the method for forming an interface modification layer between the solid electrolyte and the negative electrode sheet can be one of the following three: (1) sequentially depositing a fluoride modification layer and a phosphide modification layer on the surface of the solid electrolyte; (2) sequentially depositing a phosphide modification layer and a fluoride modification layer on the surface of the negative electrode sheet; (3) depositing a fluoride modification layer on the surface of the solid electrolyte and a phosphide modification layer on the surface of the negative electrode sheet. All three methods can form an interface modification layer between the solid electrolyte and the negative electrode sheet relatively quickly.
[0029] Preferably, the method for forming the interface modification layer includes at least one of magnetron sputtering, vapor deposition, solution impregnation, and spin coating. That is, both the fluoride modification layer and the phosphide modification layer in the interface modification layer can be rapidly formed by at least one of magnetron sputtering, vapor deposition, solution impregnation, and spin coating.
[0030] In some embodiments, the surface of the solid electrolyte near the negative electrode is a first side surface, and the surface of the negative electrode near the solid electrolyte is a second side surface; step S2 includes: Step S21: A fluoride modification layer is formed on the first side surface by magnetron sputtering to obtain the modified first side surface; Step S22: Spin-coat a phosphide solution onto the second side, remove the solvent to form a phosphide solid film, and then perform vacuum drying to form a phosphide modification layer on the second side, thus obtaining the modified second side. Step S23: Adhere the first side modified with solid electrolyte and the second side modified with negative electrode to obtain an intermediate.
[0031] In the technical solution of this invention, a fluoride modification layer is first formed by magnetron sputtering on the first side of the solid electrolyte, ensuring a relatively uniform distribution of fluoride on the first side and guaranteeing sufficient fluorine content. Subsequently, a phosphide solution is spin-coated onto the second side of the negative electrode, and the solvent is removed to ensure a uniformly adhered phosphide solid film on the second side. Then, vacuum drying and heat treatment are performed to allow the phosphide solid film and the lithium metal of the negative electrode to fully react and form Li3P, ensuring the phosphide modification layer contains a significant amount of Li3P. Finally, the side of the solid electrolyte modified with the fluoride modification layer and the side of the negative electrode modified with the phosphide modification layer are bonded together to prepare an intermediate. This preparation method ensures sufficient fluorine and Li3P in the interface modification layer, thereby effectively improving the critical current density of the battery and reducing interface impedance, thus improving the battery's cycle performance.
[0032] In some embodiments, in step S21: the pressure of the magnetron sputtering method is 0.5~1.0 Pa; and / or, the power of the magnetron sputtering method is 25~35 W; and / or, the time of the magnetron sputtering method is 250~350 s. That is, the pressure of the magnetron sputtering method can be 0.5 Pa, 0.8 Pa, or 1.0 Pa, the power of the magnetron sputtering method can be 25 W, 30 W, or 35 W, and the time of the magnetron sputtering method can be 250 s, 300 s, or 350 s. Controlling the pressure, power, and time of the magnetron sputtering method within the above ranges can ensure that the fluoride modification layer formed on the first side is relatively dense and uniform.
[0033] In one embodiment, in step S22: the spin coating includes spin coating at 550-650 rpm for 8-12 seconds, followed by spin coating at 2500-3500 rpm for 25-35 seconds; and / or, the concentration of the phosphide solution is 0.05-0.1 M; and / or, the phosphide in the phosphide solution includes at least one of triphenylphosphine and trioctylphosphine; and / or, the vacuum drying process includes heating from 20-25°C to 80-120°C and holding at that temperature for 25-35 minutes, followed by heating to 125-135°C and holding at that temperature for 1.5-2.5 hours. That is, the rotation speed of low-speed spin coating can be 550 rpm, 600 rpm, or 650 rpm, and the low-speed spin coating time can be 8 s, 10 s, or 12 s; the rotation speed of high-speed spin coating can be 2500 rpm, 3000 rpm, or 3500 rpm, and the high-speed spin coating time can be 25 s, 30 s, or 35 s; the concentration of phosphide in the phosphide solution can be 0.05 M, 0.07 M, or 0.1 M; the phosphide in the phosphide solution can be any one or both of triphenylphosphine and trioctylphosphine; the initial temperature of vacuum drying treatment can be 20℃, 22℃, or 25℃; the temperature of the first heating in vacuum drying treatment can be 80℃, 100℃, or 120℃; the holding time of the first heating can be 25 min, 30 min, or 35 min; the temperature of the second heating can be 125℃, 130℃, or 135℃; and the holding time of the second heating can be 1.5 h, 2 h, or 2.5 h. Simultaneously controlling the above conditions within a suitable range can ensure that the phosphide solution is relatively uniformly spin-coated onto the second side, and after vacuum drying, the phosphide film can react more fully and thoroughly with the lithium metal of the negative electrode sheet to convert into Li3P.
[0034] The present invention also provides an electrical device comprising the aforementioned battery cell or a battery cell prepared by the aforementioned method for preparing the battery cell. Therefore, this electrical device possesses all the beneficial effects of the aforementioned battery cell or the aforementioned method for preparing the battery cell, which will not be elaborated upon here.
[0035] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0036] Example 1 A single battery cell is prepared by the following steps: Step S1: Solid electrolyte treatment (1) The halide solid electrolyte Li2ZrCl6 was pressed into a dense sheet with a thickness of 1 mm. Then the surface was cleaned with anhydrous ethanol to remove possible adsorbed impurities. Then it was placed in a vacuum drying oven at 60°C for 2 h to obtain the pretreated solid electrolyte sheet. (2) The pretreated solid electrolyte sheet was placed in the sputtering chamber. A high-purity (≥99.9%) LiF ceramic target was used as the target material. The sputtering chamber was evacuated to minimize the contamination of the film by residual gas. High-purity argon gas was introduced as the sputtering gas. The working pressure was set at 1.0 Pa. An RF power supply was used with a power range of 30 W. The deposition time was 300 s. After deposition, the film was left to stand for 20 minutes (to ensure the stability of the modified layer) and then taken out to the glove box to obtain the modified solid electrolyte (the fluoride modified layer is LiF with a thickness of 20 nm). Step S2: Negative electrode plate processing (1) Using a 50μm thick lithium foil, the surface of the lithium foil was wiped twice with anhydrous cyclohexane to remove most of the oxide layer and impurities, and the pretreated lithium foil was obtained. (2) Immediately transfer the pretreated lithium foil to the substrate to be used, use a pipette to draw 10 μL of 0.05 MPa Ph3 solution (solvent is tetrahydrofuran), and evenly drop the solution onto the central area of the lithium foil. Then place the lithium foil on a spin coater and rotate it at a low speed of 600 rpm for 10 s to allow the solution to spread initially. Then rotate it at a high speed of 3000 rpm for 30 s to form a uniform film on the surface of the lithium foil. (3) After spin coating, the lithium foil was left to stand for 15 minutes to allow the solvent to evaporate completely, leaving a uniform PPh3 solid film on the surface of the lithium foil. Then, the lithium foil was placed in a sealed transfer chamber in a glove box and transferred to a vacuum drying oven for heat treatment. The specific steps were as follows: the temperature was raised from 25°C to 100°C and kept at that temperature for 30 minutes. Then, the temperature was raised to 130°C and kept at that temperature for 2 hours to allow PPh3 to decompose and form a Li3P coating. After natural cooling, the sample surface was gently rinsed twice with anhydrous dimethyl ether to remove the reaction byproducts. Finally, the modified negative electrode sheet was obtained (the phosphide modification layer is Li3P and the thickness of the phosphide modification layer is 50 nm). Step S3: Assemble a symmetrical cell (Li|Li3P-LiF|Li2ZrCl6|LiF-Li3P|Li), in which both the positive and negative electrodes are coated lithium metal sheets.
[0037] Example 2 The difference between Example 2 and Example 1 is that: The thickness of the fluoride-modified layer is 30 nm.
[0038] Example 3 The difference between Example 3 and Example 1 is that: The thickness of the fluoride-modified layer is 15 nm.
[0039] Example 4 The difference between Example 4 and Example 1 is that: The thicknesses of the phosphide-modified layer and the fluoride-modified layer are 400 nm and 100 nm, respectively.
[0040] Example 5 The difference between Example 5 and Example 1 is that: The thicknesses of the phosphide-modified layer and the fluoride-modified layer are 20 nm and 5 nm, respectively.
[0041] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that: Only a fluoride-modified layer is applied, with a thickness of 70 nm.
[0042] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that: Only a phosphide modification layer is applied, with a thickness of 70 nm.
[0043] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that: A phosphide modification layer is provided on the surface of the solid electrolyte, and a fluoride modification layer is provided on the surface of the negative electrode.
[0044] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that: No interface modification layer is placed between the solid electrolyte and the negative electrode.
[0045] Comparative Example 5 Comparative Example 5 differs from Example 1 in that: A phosphide and fluoride co-doped modification layer with a thickness of 70 nm was deposited on the surface of the negative electrode using a sputtering method. The specific steps are as follows: (1) Select a lithium foil with a flat surface and gently wipe its surface with anhydrous organic solvent (such as anhydrous hexane or xylene) to remove the oxide layer and impurities formed during transportation and storage; (2) Install high-purity (≥99.9%) LiF and Li3P ceramic targets onto different target positions in the magnetron sputtering cavity; (3) Evacuate to high vacuum: Evacuate the cavity to a background vacuum level better than 5.0 × 10⁻⁶. -5 This ultra-high vacuum environment is necessary to maximize the removal of residual water vapor and oxygen in the cavity, so as to avoid contamination of the active lithium sheet surface. (4) Introduce working gas: After the background vacuum reaches the standard, introduce high-purity argon (Ar, purity 99.999%) into the cavity as the working gas, and stabilize the pressure in the cavity at 0.5 to 1.0 Pa; (5) Start the RF power supply of LiF target and Li3P target respectively to start co-sputtering; set the power range to 30W, the deposition time to 300s, and let stand for 20 minutes after deposition (to ensure the stability of the modified layer).
[0046] Performance testing The following tests were performed on the symmetric cells prepared in Examples 1-5 and Comparative Examples 1-5: (1) Interface impedance: Connect the assembled symmetrical cell to the electrochemical workstation, apply a sinusoidal voltage signal with a small amplitude (5mV) near the open circuit potential of the cell, and scan the frequency range from high frequency (1 MHz) to low frequency (0.1 Hz) to obtain the electrochemical impedance spectrum and analyze it to obtain the interface impedance; (2) Critical Current Density (CCD): A stepwise increasing current density is applied to the symmetrical battery through the battery charging and discharging system, starting from 0.1 mA / cm². 2 Initially, constant current cycling was performed at each current density for a period of time (30 min), then at a fixed step size (0.1 mA / cm). 2 Increase the current density and monitor the voltage-time curve in real time. When the voltage shows severe noise, sudden drop or sudden short circuit characteristics, it indicates that a large number of lithium dendrites have been generated and will soon lead to an internal short circuit. The stable current density value before the short circuit occurs is the critical current density of the battery. (3) Cycle life: Solid-state batteries LFP|Li2ZrCl6|LiF-Li3P|Li were assembled using lithium iron phosphate (LiFePO4) cathode material. The assembled full cells were allowed to stand for 4 hours to allow the system to reach equilibrium. Activation was performed for 3 cycles at a rate of 0.1C / 0.1C. After activation, long-term charge-discharge cycle tests were conducted at a rate of 1C, and the cycle life was determined with the battery capacity retention rate below 80%. Furthermore, the surface morphology of the lithium metal anode of the full cells corresponding to Example 1 and Comparative Example 4 was observed after 50 cycles at 1C, and the results are as follows: Figure 1 and Figure 2 As shown.
[0047] The test results are shown in Table 1.
[0048] Table 1. Performance characterization of symmetric cells prepared in Examples 1-5 and Comparative Examples 1-5
[0049] Based on Table 1, the following analysis is performed: The high interfacial impedance of Comparative Example 4 is mainly due to the in-situ formation of a complex, loosely structured, and unevenly thick solid electrolyte interface (SEI) during the early charging and discharging process of the battery. Its main component is LiCl, which has extremely poor ionic conductivity, which inhibits the migration rate of lithium ions. At the same time, due to its uneven composition, there are some sites with incomplete electronic insulation, which leads to the occurrence of side reactions and ultimately results in a low critical current density. Compared with Comparative Example 4, an interface modification layer is provided between the solid electrolyte and the negative electrode in Examples 1-5 and Comparative Examples 1, 2, 3, and 5. Therefore, the interface impedance of the corresponding battery cells is reduced, and the critical current density and cycle life are increased. Comparing Comparative Example 1 and Example 1, it was found that replacing the phosphide modification layer with a fluoride modification layer, i.e., the entire interface modification layer being fluoride, significantly increased the interfacial impedance, mainly due to the presence of fluoride. - With Li + Strong ionic bonds easily form between them, hindering Li + Migration and diffusion; however, the addition of a fluoride modification layer can effectively increase the critical current density, mainly because the fluoride formed at the interface is a dense and uniform coating with excellent electronic insulation, fundamentally suppressing the side reactions of SEI and the deposition of lithium metal on the negative electrode surface; by Figure 1 and Figure 2 As shown, the surface morphology of the full cell negative electrode corresponding to Comparative Example 4 is rough, while the surface morphology of the full cell negative electrode corresponding to Example 1 is smooth and there is no obvious lithium dendrite formation. Comparing Comparative Example 2 and Example 1, it was found that replacing the fluoride modification layer with a phosphide modification layer, i.e., the entire interface modification layer is made of phosphide, resulted in a lower interface impedance of the battery cell, but its critical current density did not increase significantly, and the corresponding improvement in the cycle life of the assembled full cell was not significant. Among them, the phosphide modification layer can effectively reduce the interface impedance, mainly because it has good ionic conductivity, which can effectively and uniformly distribute lithium ions, avoid uneven lithium deposition, and improve its safety. Comparing Comparative Example 3 and Example 1, it was found that setting a fluoride modification layer on the solid electrolyte side and a phosphide modification layer on the negative electrode side can significantly reduce the interfacial impedance of the battery cell and increase the critical current density, effectively suppress lithium dendrite growth, and improve the cycle stability and cycle life of the battery cell. However, in Comparative Example 3, when a fluoride modification layer is set on the negative electrode side and a phosphide modification layer is set on the solid electrolyte side, the poor ionic conductivity of the LiF layer in contact with lithium becomes a bottleneck for ion transport, and the advantages of the phosphide modification layer cannot be fully utilized. The decrease in critical current density is mainly due to the low ionic conductivity of the fluoride portion limiting the migration rate of lithium ions from the negative electrode to the electrolyte, inducing uneven lithium deposition and forming lithium dendrites. Once the lithium dendrites penetrate the fluoride modification layer, there are no dendrite suppression measures. Comparing Comparative Example 5 with Comparative Example 4 and Example 1, it was found that setting a fluoride and phosphide co-doped modification layer between the solid electrolyte and the negative electrode can reduce the interfacial resistance and slightly increase the critical current density to a certain extent. This is mainly due to the random distribution of Li3P and LiF particles in the co-doped layer. + When lithium ions pass through the blended doped layer, they tend to be conducted from the Li3P phase, resulting in an uneven distribution of ion current density on the lithium metal surface. This increases the tortuosity of the ion transport path, increases the migration barrier, and easily forms a "sharp effect" in local high ion current regions, inducing non-uniform nucleation of lithium dendrites. In addition, suppressing dendrites requires a continuous and dense electron barrier layer. However, in the blended layer, LiF is dispersed in an "island" shape, making it difficult to form a continuous electron shielding barrier. Therefore, the cycle life of the full cell corresponding to Comparative Example 5 is still relatively low. A comparison of Examples 1-5 revealed that when the thickness ratio of the fluoride-modified layer to the phosphide-modified layer reached 5:3 to 10:3 (i.e., 1.6 to 3.3), the improvement effect on cycle life, interfacial impedance, and critical current density was the best. When the thickness ratio exceeded this range, and the LiF layer was too thick, it would hinder the Li... + Transmission impedance increases significantly. When LiF is too thin, the formed electron shielding barrier is weak, dendrites can easily penetrate, and the critical current density and cycle life performance are poor. When LiP is too thick, ions are restricted due to the long conduction path, and there is a problem of coating cracking. When LiP is too thin, it is easy to cause the coating to be discontinuous, which cannot effectively homogenize the lithium flow, and local point dendrites are easy to nucleate and form lithium dendrites.
[0050] In summary, Example 1 exhibits low interfacial impedance and high critical current density. The asymmetric coating of phosphide and fluoride achieves a 1+1>2 effect. On the one hand, Li3P homogenizes the lithium-ion flow, guiding lithium to deposit uniformly from the source and suppressing dendrite nucleation. On the other hand, the electronic insulation of the LiF layer acts as the final barrier to suppress lithium dendrite growth, ultimately improving the battery cycle performance.
[0051] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.
Claims
1. A battery cell, characterized in that, The battery cell includes a positive electrode, a negative electrode, an interface modification layer, and a solid electrolyte. The interface modification layer is disposed between the solid electrolyte and the negative electrode. The negative electrode includes elemental lithium metal. The interface modification layer includes a phosphide modification layer and a fluoride modification layer, wherein the phosphide modification layer is disposed on the side of the fluoride modification layer close to the negative electrode sheet; The phosphide-modified layer includes a Li3P layer, and the fluoride-modified layer includes a LiF layer.
2. The battery cell as described in claim 1, characterized in that, The thickness of the phosphide-modified layer is 20 nm to 400 nm.
3. The battery cell as described in claim 1, characterized in that, The thickness of the fluoride-modified layer is 5 nm to 100 nm.
4. The battery cell as described in claim 1, characterized in that, The thickness ratio of the phosphide-modified layer to the fluoride-modified layer is 5:3 to 10:3; and / or, The solid electrolyte includes at least one of halide solid electrolyte, sulfide solid electrolyte and oxide solid electrolyte, wherein the halide solid electrolyte includes at least one of Li2ZrCl6 and Li3YCl6.
5. A method for preparing a battery cell as described in any one of claims 1 to 4, characterized in that, The method for preparing the battery cell includes the following steps: Solid electrolytes, negative electrode plates, and positive electrode plates are provided; The solid electrolyte is bonded to the negative electrode to form an intermediate; wherein an interface modification layer is formed between the solid electrolyte and the negative electrode. The intermediate and the positive electrode are assembled to obtain a battery cell.
6. The method for preparing a battery cell as described in claim 5, characterized in that, The method for forming the interface modification layer includes at least one of magnetron sputtering, vapor deposition, solution impregnation, and spin coating.
7. The method for preparing a battery cell as described in claim 5, characterized in that, The surface of the solid electrolyte near the negative electrode is the first side surface, and the surface of the negative electrode near the solid electrolyte is the second side surface. The step of bonding the solid electrolyte to the negative electrode sheet to form an intermediate includes: A fluoride modification layer is formed on the first side surface by magnetron sputtering to obtain the modified first side surface. A phosphide solution is spin-coated onto the second side, the solvent is removed to form a phosphide solid film, and then vacuum drying is performed to form a phosphide modification layer on the second side, resulting in a modified second side. The first side modified with solid electrolyte and the second side modified with negative electrode are bonded together to obtain an intermediate.
8. The method for preparing a single battery cell as described in claim 7, characterized in that, In the step of forming a fluoride modification layer on the first side surface by magnetron sputtering to obtain the modified first side surface: The pressure of the magnetron sputtering method is 0.5~1.0 Pa; and / or, The power of the magnetron sputtering method is 25~35W; and / or, The magnetron sputtering time is 250~350s.
9. The method for preparing a battery cell as described in claim 7, characterized in that, In the step of spin-coating a phosphide solution onto the second side, removing the solvent to form a phosphide solid film, and then performing vacuum drying to form a phosphide modified layer on the second side, thus obtaining the modified second side: The spin coating includes spin coating at 550-650 rpm for 8-12 seconds, followed by spin coating at 2500-3500 rpm for 25-35 seconds; and / or, The concentration of the phosphide solution is 0.05~0.1M; and / or, The phosphide solution contains at least one of triphenylphosphine and trioctylphosphine; and / or, The vacuum drying process includes heating from 20~25℃ to 80~120℃ and holding at that temperature for 25~35 minutes, followed by heating to 125~135℃ and holding at that temperature for 1.5~2.5 hours.
10. An electrical device, characterized in that, The electrical device includes a battery cell as described in any one of claims 1 to 4 or a battery cell prepared by the method described in any one of claims 5 to 9.
